Campus Sports Facilities and Exercise Motivation Predict Students’ Physical Activity Participation (COMPETITOR: Jurnal Pendidikan Kepelatihan Olahraga, 2026)
This study examined whether campus sports facilities and exercise motivation predict students' participation in structured physical activity. A quantitative cross-sectional survey was analysed through a hierarchical regression approach in which demographic controls were entered before campus sports facilities and exercise motivation. Campus sports facilities were represented by students' perceptions of adequacy, accessibility, maintenance, safety, and timetable suitability, while exercise motivation reflected enjoyment, personal importance, competence, persistence, health value, and willingness to maintain exercise routines. The findings showed that demographic controls made only a limited contribution to explaining participation. Perceived campus sports facilities improved the prediction of participation, indicating that students were more likely to engage in structured physical activity when the campus environment provided accessible, safe, well-maintained, and conveniently scheduled sport opportunities. Exercise motivation added stronger explanatory value and emerged as the most influential predictor in the final model. Both facilities and motivation remained important when analysed together, suggesting that student participation is shaped by the interaction between institutional opportunity and personal motivational resources. The study implies that universities should integrate facility improvement with motivational programming to strengthen students' sustained involvement in structured physical activity.